Subacute Osteomyelitis of the Pediatric Talus: A First Report of Brodie’s Abscess from Morganella morganii - Mitchell C. Harris; Daniel C. DeRosa; Priscilla A. West (Case Reports in Orthopedics)
Brodie’s abscess is a subacute form of osteomyelitis which generally occurs in the metaphysis of the femur and tibia in the pediatric population. Pathogens are most commonly Gram-positive bacteria, notably Staphylococcus and Streptococcus. In this article, we describe a young pediatric patient presenting with subacute ankle pain with a subsequent diagnosis of Brodie’s abscess of the talus secondary to Morganella morganii. We review the presentation, diagnosis, and treatment of this unique patient. To our knowledge, this is the first report of Morganella morganii as a cause of Brodie’s abscess.